2002
DOI: 10.1103/physrevlett.88.036804
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Resistance versus Length in Single-Walled Carbon Nanotubes

Abstract: In this work fundamental properties of the electrical transport of single-walled carbon nanotubes as a function of their length are investigated. For this purpose, we have developed a new technique that allows us to characterize electronic transport properties of single-walled carbon nanotubes by probing them at different spots. This technique uses scanning force microscopy to make mechanical and electrical nanocontacts at any selected spot of a given image. We have applied this technique to molecules with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 25 publications
5
72
0
Order By: Relevance
“…10 This theory has been used to explain exponential length dependences of the resistance measured in nanotubes. [26][27][28] SL occurs when the phase-coherence length L becomes longer than the localization length L loc . This is equivalent to when the width of the coherent states, បv F / L , becomes smaller than the energy separation between the localized states.…”
Section: Discussionmentioning
confidence: 99%
“…10 This theory has been used to explain exponential length dependences of the resistance measured in nanotubes. [26][27][28] SL occurs when the phase-coherence length L becomes longer than the localization length L loc . This is equivalent to when the width of the coherent states, បv F / L , becomes smaller than the energy separation between the localized states.…”
Section: Discussionmentioning
confidence: 99%
“…A metallic AFM tip was used to measure the current vs. voltage characteristics (IV) of the nanotubes as a function of the distance between the metallic AFM tip, used as mobile electrode, and a fixed macroscopic gold electrode 21 . Briefly, the experiments were performed as follows: a metallic SWNT was first selected (Fig.…”
Section: Tuning the Conductance Of Single Walled Carbon Nanotubes By mentioning
confidence: 99%
“…at room temperature. In addition, the measured low voltage resistance (LVR) data is theoretically analysed using a combination of density functional methods and Green's functions techniques.A metallic AFM tip was used to measure the current vs. voltage characteristics (IV) of the nanotubes as a function of the distance between the metallic AFM tip, used as mobile electrode, and a fixed macroscopic gold electrode 21 . Briefly, the experiments were performed as follows: a metallic SWNT was first selected (Fig.…”
mentioning
confidence: 99%
“…(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)] and Poisson iterations of [Eqs. (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)] for the potential profile and charge distribution. Typically, 3 − 5 Born iterations were performed before updating a potential profile using Eq.…”
Section: Formalismmentioning
confidence: 99%
“…Therefore, * Electronic address: svizhenk@nas.nasa.gov † Electronic address: anant@mail.arc.nasa.gov both small and large diameter nanotubes are promising as interconnects. Experiments on small diameter carbon nanotubes show that the differential conductance decreases with applied bias, for voltages larger than 150 mV [9,10,11]. Reference [9] showed that the conductance decreases with increase in bias was caused by reflection of electrons incident in crossing subbands due to scattering with zone boundary phonons.…”
Section: Introductionmentioning
confidence: 99%